The Role of English Language Skills in the Tourism Industry in the 4.0 Era in Kuningan District, West Java Province - Oktoma, Erwin; Solihat, Dadang; Masruroh, Rina (International Journal Administration, Business & Organization, 2024)
Through communication media, English plays a significant role in the sustainable tourism sector with the goal of promoting foreign travel, service, effective communication between foreign visitors and tourism actors, and the surrounding community, all of which are ultimately related to the growth of local tourism in the industrial era's sustainable tourism sector. 4.0 Tourist actors need to be fluent in English, especially in the vernacular, which includes basic discussion, linguistic proficiency, and basic conversation. The purpose of this study is to investigate the advantages of English- speaking culture in West Java Province's sustainable tourism sector during the Industrial Era 4.0. Descriptive qualitative analysis is the analytical technique employed. This study demonstrates the necessity of English-speaking culture in Kunuingan District, West Java Province's sustainable tourism industry in the industrial era 4.0 in order to promote the province's local tourist destinations overseas, increase the number of foreign visitors, and facilitate English-language communication. The ability to speak effectively in English is crucial for both those who work in the tourism business and those who live near popular tourist sites.